Proporción de carbón vegetal en la resistencia a la compresión de adobe artesanal. Loreto - Pacaya Tuanama, Norma Adela (2024)
The objective of this research was to evaluate the effect of the proportion of ground charcoal on the compressive strength of handmade adobe in Loreto. An experimental design was used with four treatments: 0%, 10%, 20%, and 30% of ground charcoal mixed with soil, with 5 repetitions. Compression strength tests were conducted by measuring the force in kilonewtons (kN) and kilograms (Kg), surface area (cm²), and stress (Kg/cm²). The results showed that the addition of ground charcoal significantly improves the compressive strength of adobe. Analysis of variance (ANOVA) indicated that the observed differences were significant (p < 0.0001) with an adjusted R² of 0.81 for force and 0.68 for stress, demonstrating a strong relationship between the proportion of charcoal and adobe strength. The Tukey test revealed that adobe with 20% ground charcoal could withstand up to 41.69 kN and 4250.99 Kg, while adobe without charcoal could withstand 29.59 kN and 3017.54 Kg. However, no significant differences were found in the surface area (cm²). In conclusion, the 20% proportion of ground charcoal optimizes the strength and durability of handmade adobe, making the material more robust for structural applications. It is recommended to continue exploring additional materials that can further enhance these properties, especially for rural construction.